2002
DOI: 10.1152/ajpgi.00025.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role ofpp60c-srcandp44/42MAPK in ANG II-induced contraction of rat tonic gastrointestinal smooth muscles

Abstract: (46, 49, 51). Limited information is available on the actions and signal transduction mechanisms of ANG II in the gastrointestinal smooth muscle, specifically the tonic smooth muscles of sphincters. Lower esophageal sphincter (LES) and internal anal sphincter (IAS) smooth muscles play an important role in the pathophysiology of a number of gastrointestinal motility disorders characterized either by the hypo-or hypertensive sphincteric smooth muscles (36,44).It is well known that a majority of the sphincteric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…We found that AngII induced a rapid elevation in phosphorylation of ERK1/2 and caldesmon. This is consistent with the previous studies in rat gastrointestinal smooth muscles [19]. AngIIevoked contraction in both VSMCs and aortic rings was attenuated by PD98059, indicating that AngIIinduced VSMC contraction was dependent on ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 93%
“…We found that AngII induced a rapid elevation in phosphorylation of ERK1/2 and caldesmon. This is consistent with the previous studies in rat gastrointestinal smooth muscles [19]. AngIIevoked contraction in both VSMCs and aortic rings was attenuated by PD98059, indicating that AngIIinduced VSMC contraction was dependent on ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 93%
“…In summary, present data combined with the potent contractile effect of ANG II (17,27,33), presence of AT 1 -R (35), the corresponding signal transduction cascade (31,34) in the IAS SMC, and fall in the IAS tone by ANG II biosynthesis inhibitors suggest that RAS, in part, may regulate basal tone in the IAS. The other extracellular signals for the balance of the basal tone may be prostanoids (6,7).…”
Section: Discussionmentioning
confidence: 54%
“…Earlier studies in the IAS have demonstrated the presence of ANG II and AT 1 receptors (14,17,31). However, the major part of the RAS in the IAS SMC has not been investigated.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…ERK1/2 and p38 MAPK have been previously reported to play a role in contraction of both vascular (37,41) and intestinal smooth muscle (6). The phosphorylation of caldesmon and/or calponin is thought to be one mechanism whereby ERK1/2 contributes to smooth muscle contraction (26,31).…”
Section: Discussionmentioning
confidence: 99%